Gender-inclusive governance of “self-help” groups in rural Kenya - Aberman, Noora-Lisa; Birner, Regina; Odoyo, Elizabeth Auma Okiri; Oyunga, Mary Anyango; Okoba, Barrack; Okello, George Otiep (International Food Policy Research Institute, 2020)
There is vast literature on groups as a useful mechanism for rural development, especially for women. However, for group participation to fulfil on potential benefits to women, gender-specific constraints must be addressed. This study examines how to promote gender-inclusive governance of mixed-sex self-help groups in the African context, analysing twenty mixed-sex focus group discussions with 190 group members in rural western Kenya. Emphasizing group member perceptions and beliefs about participation and governance, we undertake an empirical assessment of institutional factors that explain and facilitate effective participation of female members. We find that group-member endowments impact the group’s interpretation in terms of their understanding of gender issues and political processes, and that the pro-gender intentions behind governance structures are more important than the structures themselves. Furthermore, groups in this context serve as a distinct parallel institution to that of the home that enable them to push the boundaries of community gender norms.